(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
We interviewed the director, playwright and performer Carolina Bianchi. In this interview, we talked about her latest work, Cadela Força - Chapter I: A Noiva e o Boa Noite Cinderela, and we discussed aspects of the creative process that focus on the theme of sexual violence. Other aspects of this creation are also included in this discussion, such as the challenge of collective work at a distance and different forms of production in the Brazilian context and in the European context in which Bianchi currently finds herself.